WHAT DO OUR STUDENTS WANT? A CASE STUDY OF EFL SPEAKING STUDENTS’ VIEW OF ACTIVITIES IN SPEAKING CLASSROOM - Hijjatul Qamariah (English Education Department, 2017)
Students’ beliefs or perspectives have been essential inputs for reflection and improvement of the teaching and learning of English. Knowing their interest and what they want will lead to a better and effective teaching and learning process. Thus, this case study attempted to find out the students’ view of activities in the speaking classroom. Students’ perspective and ideas toward activities, teachers’ role and students’ interest in topic and materials in speaking classroom are identified. To achieve this objective, 12 students were involved. The data were obtained through the interviews with the students who took speaking class. The interview was conducted by using focus group interview. Findings revealed that most of communicative activities such as drama, role play, storytelling, group works, dialogue, etc should be applied in speaking classroom. The involvement of teacher in speaking activities was also crucial, most of the students stated that teacher should make rule and always keep the target of the activities. In addition, teachers should always provide feedback and motivation, and also perform punishment and rewards practice. Results also indicated that in order to be able to speak and think more creative, students suggested authentic materials and familiar but also challenging topics should be provided. Moreover, topic such as current issues, tourism, lifestyle and history were also chosen by them as topics they are interested to learn.